Peningkatan Produktivitas Tanaman Hortikultura Melalui Smart Watering System di Kelurahan Klasuluk Provinsi Papua Barat Daya - Sahiruddin; Ratna Prabawati; Aci Aprianto; Petronela Jare; Kundrat agustinus Karay (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Klasuluk Village is one of the villages in Mariat District, Sorong Regency, Southwest Papua. In general, the people of Klasuluk Village work as farmers. The commodities most widely planted by the people of Klasuluk Village are horticultural plants. Dry soil conditions and watering systems that still use manual equipment are the causes of low horticultural plant productivity in Klasuluk Village, especially the Tunas Siaga farmer group. The methods of implementing this community service are (1) Socialization, (2) training, (3) application of technology, (4) mentoring and program evaluation. The results of this community service program are the application of smart watering system technology and training in the use of this technology can increase the productivity of horticultural plants and increase the economic value of the community in Klasuluk Village in the Tunas Siaga farmer group. From the results of this community service program, it can be concluded that smart watering system technology can increase the productivity of horticultural plants and is very much needed by the Tunas Siaga farmer group.